ANALISIS NILAI KONTRIBUSI BADAN AMIL ZAKAT NASIONAL (BAZNAS) UNTUK PROGRAM KEMANUSIAAN PALESTINA TAHUN 2018-2021 - Abdi Ridho, Muhammad; Ibdalsyah, Ibdalsyah; Ayuniyyah, Qurroh (Kasaba, 2023)
Palestine is located in the Southwest Asia region. Diplomatic relations between Indonesia and Palestine have been established since the early days of Indonesia's independence. Palestine is one of the holiest places in Islam. On the other hand, Indonesia is a country with the largest Muslim population in the world. This situation creates a strong emotional bond between Indonesia and Palestine. Since the Jews declared the establishment of the state of Israel in the Palestinian territories in 1948, Indonesia has been part of the party opposing the Israeli occupation and supporting the Palestinian people's efforts to gain their right to independence. The support of the Indonesian people for Palestine continues. In terms of humanitarian assistance, zakat, infaq and alms management institutions (ZIS) are increasingly aggressively promoting various humanitarian aids, one of which is the National Amil Zakat Agency (BAZNAS). This study aims to analyze the value of the contribution and distribution of the allocation of zakat, infaq and alms funds by BAZNAS for humanitarian aid in Palestine. In addition, this study also wants to measure the effectiveness of the distribution of ZIS funds at BAZNAS. The sampling method used in this research is purposive sampling method. Quantitative data were analyzed using basic statistical calculations and the zakat core principles (ZCP) approach. While qualitative data is described using descriptive analysis method. The results of this study indicate that the value of the contribution to the distribution of ZIS funds for Palestinian humanitarian assistance carried out by BAZNAS in 2018-2021 is volatile.